Looking back, looking forward : reality check by journalists in Sri Lanka - Ibrahim, Hana.; Family Planning Association of Sri Lanka; ICPD Programme of Action (Colombo : Family Planning Association of Sri Lanka, 2006)
Articles on the social conditions of Sri Lanka.
'ICPD Programme of Action'--Cover.
Keywords: Sri Lanka -- Social conditions